The Efficiency of Wemco Drums at Kleinkopje Coal Washing Plant Over 30 Years - T. T. Matuludi (The Southern African Institute of Mining and Metallurgy, 2010)
Kleinkopje Colliery has five Wemco drums that were installed and commissioned in 1978. Over the years, there have been remarkable changes in mining and geological conditions at the colliery. First, an increase in the percentage of fines was recorded, which resulted in an uneven split or an imbalance in silo levels between material feeding the cyclone (-12 mm) and Wemco drum (+12 mm) sections respectively. This problem was solved by doing modifications around the banana screens to allow finer material to the drums. The imbalance challenge was then followed by spontaneous combustion that takes place in situ and results in low product yield. The results obtained from efficiency tests indicate that although there is a limit in the percentage of -6 mm material in the feed, Wemco drums are still very efficient and applicable to the current mining conditions. These results also suggest that it is essential to lower the throughput when the drums are treating low yielding coal.